Enhanced antiadhesive properties of chitosan/hyaluronic acid polyelectrolyte multilayers driven by thermal annealing : Low adherence for mammalian cells and selective decrease in adhesion for Gram-positive bacteria - Muzzio, Nicolás Eduardo (2017)
The development of antifouling coatings with restricted cell and bacteria adherence is fundamental for many biomedical applications. A strategy for the fabrication of antifouling coatings based on the layer-by-layer assembly and thermal annealing is presented. Polyelectrolyte multilayers (PEMs) assembled from chitosan and hyaluronic acid were thermally annealed in an oven at 37 °C for 72 h. The effect of annealing on the PEM properties and topography was studied by atomic force microscopy, ζ-potential, circular dichroism and contact angle measurements. Cell adherence on PEMs before and after annealing was evaluated by measuring the cell spreading area and aspect ratio for the A549 epithelial, BHK kidney fibroblast, C2C12 myoblast and MC-3T3-E1 osteoblast cell lines. Chitosan/hyaluronic acid PEMs show a low cell adherence that decreases with the thermal annealing, as observed from the reduction in the average cell spreading area and more rounded cell morphology. The adhesion of S. aureus (Gram-positive) and E. coli (Gram-negative) bacteria strains was quantified by optical microscopy, counting the number of colony-forming units and measuring the light scattering of bacteria suspension after detachment from the PEM surface. A 20% decrease in bacteria adhesion was selectively observed in the S. aureus strain after annealing. The changes in mammalian cell and bacteria adhesion correlate with the changes in topography of the chitosan/hyaluronic PEMs from a rough fibrillar 3D structure to a smoother and planar surface after thermal annealing.